Multi-modal switching in responsive DNA block co-polymer conjugates - YAŞAYAN, GÖKÇEN (ROYAL SOC CHEMISTRY, 2013)
New classes of information-rich DNA block co-polymer conjugates were synthesised, encoded with thermoresponsive and biocompatible poly(tri(ethylene glycol) ethyl ether methacrylate) (pTriEGMA) chains and oligomeric nucleic acids connected by either bioreducible or non-reducible links. The pTriEGMA chains were grown from initiator-functionalised hybridised DNA, designed to assemble with toehold overhangs. Functional information in the conjugates was explored via dynamic light scattering (DLS) and atomic force microscopy (AFM), in order to evaluate (i) reversible self-assembly into supramolecular structures across the pTriEGMA phase transition temperature; (ii) conformational change via addition of competing DNA sequences across the toeholds, and (iii) reductive cleavage of polymer-DNA links. The results showed that discrete nanoscale conjugates could reversibly associate through pTriEGMA phase behaviour and that size and association behaviour in one class of conjugate could be switched by addition of a competing DNA sequence and by reduction to break the polymer-DNA links. Preliminary experiments with the DNA-conjugates as delivery systems for doxorubicin to a cancer cell line indicated good tolerability of the conjugates alone and cytotoxic efficacy when loaded with the drug.
Keywords: SYNTHETIC-POLYMERS; DRUG-DELIVERY; ORIGAMI; DOXORUBICIN; MICELLES; HYDROGEL